Legal Protection From Creditors As The Fiduciary Security In A Financing Associated With The Award Mahkamah Konstitusi No. 18/PUU-XVII/2019 - Gultom, Hawer Trimaryanto (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2021)
Abstract: The background of this research is that the fiduciary guarantee is a form of legal protection for creditors as the holder of the fiduciary guarantee in the management agreement regulated in Article 15 of Law No. 42 of 1999 concerning Fiduciary Guarantee. However, after the issuance of the Constitutional Court Decision Number 18 / PUU-XVII / 2019 which considers the provisions of article 15 of the fiduciary guarantee Act regarding the executorial power of fiduciary recipients who will abuse creditors, or in other words the fiduciary guarantee certificate has no legal certainty. in the power of execution. Therefore, the aim of this study is to analyze the legal certainty and protection of the execution of fiduciary guarantees in the agreement regulated by the Decision of the Constitutional Court Number 18 / PUU-XVII / 2019. This research is a normative juridical study but is also supported by empirical data so that it is researched data that comes from literature and court decisions. The results show that the legal certainty of the Fiduciary Guarantee Parate in the Financing Agreement is linked to the Constitutional Court Decision Number 18 / PUU-XVII / 2019, namely that creditor companies can still execute fiduciary objects as long as there are provisions for default or default in the agreement of the parties as outlined in the deed. agreement and the debtor’s willingness to submit the object of guarantee. The form of legal protection for creditors as holders of fiduciary guarantees is linked to the Constitutional Court Decision Number 18 / PUU-XVII / 2019 in a preventive manner, namely by making a financing agreement as outlined in a deed and containing provisions related to default or default. Meanwhile, repressive legal protection is that if the debtor does not admit to default, the creditor can file a lawsuit against the court, so that the court will determine the condition of the debtor’s default. Keywords: Legal Protection, Fiduciary Guarantee, Financing Agreement